Unsolicited infrastructure proposals : how some countries introduce competition and transparency - Hodges, John T. (World Bank, Washington, DC, 2012)
This edition of Gridlines discusses how unsolicited proposals may contribute to the overall infrastructure goals of countries, particularly where governments have limited technical and financial capacity to develop projects. It also points out those unsolicited proposals can pose challenges and risks, particularly when projects are negotiated with the original proponent without sufficient transparency or competition. Channeling all unsolicited proposals into a transparent, competitive process that gives other companies a fair chance of winning the tender can reduce the risks while preserving the potential for innovative solutions.